KEBERADAAN AHLI DAN IMPLIKASI NEGATIFNYA TERHADAP ASAS PERADILAN CEPAT, SEDERHANA DAN BIAYA RINGAN (SUATU KRITIK TERHADAP PEMERIKSAAN AHLI DALAM PERADILAN PIDANA DI INDONESIA) (THE PRESENCE OF EXPERT AND THE IMPLICATION TO THE PRINCIPLE OF FAST, SIMPLE AND LOW COST JUDICIAL PROCESS) - Lucky Raspati (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2012)
The entering of an expert into a criminal trial is actually not something that just allowed. Judges as the administrative authority in the court granted the right to accept or reject an expert who wants to give their opinion before the trial. Judges act as the gate keeper to assess whether the expert possesses the competence or not in order to help the judges or juries in finding material truth so that a fair decision can be enforced. In this research, the focus problems limited to issues, first, whether the expert examination in a criminal trial was in line with the search for material truth? And second, how is the implication of expert examination to the principle of simple, fast and low cost in criminal trial? The result of the study found that the examination of an expert in a trial is not in line with basic foundation and the aim of the creation of expert witness as one of evidence in criminal procedure. Thus, it is not surprising that the presence of an expert in a criminal trial often does not help judges in finding material truth. Along with these circumstances, the presence of an expert in a criminal trial in practice today tends to be contrary with the principle of justice is fast, simple and low cost. This condition is detrimental to the accused, the prosecutors and the judges itself.ABSTRAKMasuknya seorang ahli ke dalam suatu persidangan perkara pidana sesungguhnya bukan sesuatu hal yang diperbolehkan begitu saja. Hakim sebagai pemegang kekuasaan administratif di pengadilan diberikan kewenangan untuk menerima atau menolak seorang ahli yang ingin memberikan opininya di hadapan persidangan. Hakim bertindak sebagai gate keeper untuk menilai apakah ahli tersebut mempunyai kompetensi atau tidak dalam hal membantu hakim atau juri dalam menemukan kebenaran materiil, sehingga keputusan yang adil bisa ditegakkan. Dalam penelitian ini, fokus permasalahan dibatasi, pertama, apakah pemeriksaan ahli di dalam suatu persidangan perkara pidana sudah sejalan dengan upaya mencari kebenaran materiil? dan kedua, bagaimanakah implikasi pemeriksaan ahli terhadap asas peradilan sederhana, cepat dan biaya ringan? Dari hasil penelitian ditemukan fakta-fakta bahwa pemeriksaan ahli dalam suatu perkara pidana tidak sejalan dengan fondasi dasar dan tujuan dilahirkannya keterangan ahli sebagai salah satu alat bukti dalam hukum acara pidana, sehingga menjadi tidak mengherankan kalau sekarang ini kehadiran ahli dalam suatu persidangan perkara pidana seringkali tidak membantu hakim dalam menemukan kebenaran materiil. Seiring dengan keadaan tersebut, kehadiran ahli dalam perkara pidana sekarang ini cenderung bertentangan dengan asas peradilan cepat, sederhana dan biaya ringan. Kondisi itu tentu sangat merugikan bagi terdakwa, JPU maupun Hakim itu sendiri.